2016
DOI: 10.4103/0253-7613.174418
|View full text |Cite
|
Sign up to set email alerts
|

The effect of learning styles and study behavior on success of preclinical students in pharmacology

Abstract: Objectives:To evaluate the effect of learning styles and study behaviors on preclinical medical students’ pharmacology exam scores in a non-Western setting.Materials and Methods:Grasha–Reichmann Student Learning Study Scale and a modified Study Behavior Inventory were used to assess learning styles and study behaviors of preclinical medical students (n = 87). Logistic regression models were used to evaluate the independent effect of gender, age, learning style, and study behavior on pharmacology success.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
7
1
2
Order By: Relevance
“…The study by Halil Asci et al in 2016 studied the correlations across study behaviors and learning styles and found that collaborative learning can improve students' understanding of pharmacological principles. However, gender does not seem to have any significant effect on these associations in the said group [10]. The finding of our study is in agreement with the results of the abovementioned studies wherein no correlation was found with gender.…”
Section: Discussionsupporting
confidence: 92%
“…The study by Halil Asci et al in 2016 studied the correlations across study behaviors and learning styles and found that collaborative learning can improve students' understanding of pharmacological principles. However, gender does not seem to have any significant effect on these associations in the said group [10]. The finding of our study is in agreement with the results of the abovementioned studies wherein no correlation was found with gender.…”
Section: Discussionsupporting
confidence: 92%
“…Öğrencilerin çalışma davranışları ve öğrenme stillerinde çeşitli farklılıklar olabilmektedir (7). Fakültemizde yapılan ve 2016 tarihinde yayınlanan farmakoloji dersi ile ilgili bir çalışmada, dinleyerek ve not alarak ders çalışan öğrencilerin, farmakoloji sınavından yüksek notlar aldıkları gösterilmiştir (8). Bu çalışmada da benzer olarak, öğrencilerin farmakoloji dersi çalışma stratejileri arasında not tutma, özet çıkarma, yazarak çalışma gibi aktivitelerin ön planda olduğu görülmüştür.…”
Section: Discussionunclassified
“…Çalışmamızın veri analizinde Miles ve Huberman Modeli uygulandı (8). Aşkın gerçekçilik olarak isimlendirilen bu yaklaşımın 3 bileşeni bulunmaktadır.…”
Section: Yöntemunclassified
“…6,7 Students wish to learn the topics in the following orders general pharmacology, ANS, CVS, chemotherapy because the knowledge of the topics is essential in future and the least favourite topics are autacoids, GIT, respiratory, diuretics which are mandatory. 4 Therefore, more efforts are required to make the latter topics interesting for the students.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The methodologies of teaching learning that the Department follows need to be assessed periodically so as to improve the methods of teaching. 4 Therefore, the student feedback along with perception of the teaching-learning of the students represents the primary means for the programmers/teachers to assess the quality of their methodologies of teaching with merits and demerits. 5 The objective of this study was to assess the likes and dislikes of the students about the present teaching learning methodologies and also to find out the good teaching learning methods for the rapidly updating subject.…”
Section: Introductionmentioning
confidence: 99%